2012
DOI: 10.1016/j.bbrc.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Discharge of solubilized and Dectin-1-reactive β-glucan from macrophage cells phagocytizing insoluble β-glucan particles: Involvement of reactive oxygen species (ROS)-driven degradation

Abstract: Phagocytes engulf pathogenic microbes, kill them and degrade their cellular macromolecules by hydrolytic enzymes in phagolysosomes. However, such enzymes are unable to degrade some microbial polysaccharides, and fate of such indigestible polysaccharides in phagocytes remains uncertain. Using the extracellular domain of Dectin-1 as β-glucan-specific probes, we succeeded in detection of soluble and Dectin-1-reactive β-glucan discharged from mouse RAW 264.7 and human THP-1 macrophage cell lines as well as mouse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Hino et al (2012) demonstrated that macrophages released soluble glucans into the medium after phagocytizing insoluble β-glucan particles. They found that those particles were fragmented by macrophage-produced ROS, and that the released soluble β-glucan was dectin-1-reactive and biologically active in terms of macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…Hino et al (2012) demonstrated that macrophages released soluble glucans into the medium after phagocytizing insoluble β-glucan particles. They found that those particles were fragmented by macrophage-produced ROS, and that the released soluble β-glucan was dectin-1-reactive and biologically active in terms of macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our previous study has shown the discharge of -glucan from -glucan-phagocytized macrophages. 10) The present study has shown that the plasma BG concentrations were traceable by sandwich ELISA, using recombinant rat dectin-1. In other words, the present results show that BG had affinity to rat dectin-1, suggesting that BG potentially activated such immune cells as macrophages in rats, as has been shown in mice.…”
Section: )mentioning
confidence: 48%
“…DEC-V5His expression and purification were performed as previously described. 10) The binding property of rat dectin-1 was assessed by competitive ELISA. Multi-well plate (96 wells, Nunc, Roskilde, Denmark) was coated overnight at 4 C with 125 mg/L of yeast -glucan (YG; BB-Glucan, Oriental Yeast Co., Tokyo, Japan) dissolved in 1 mol/L of NaOH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kulicke et al (1997) suggested that immunostimulating effects of β-glucans are determined by the degree of branching, length and tertiary structure of polymers, their origin, synthesis, manner of administration, dose and period of application. An increase in the concentrations of strongly oxidizing compounds (superoxide anion O 2 -, hydrogen peroxide H 2 O 2 , hydroxyl radical •OH, singlet oxygen 1 O 2 , chloramine NH 2 Cl) generated by respiratory burst was also observed by Hino et al (2012) in an in vitro study after administration of curdlan, and by Eicher et al (2010) in an in vivo experiment on calves administered the EnergyPlus supplement (mannan and β-glucan). Surprisingly, in an in vitro study by Kim et al (2004), the production of O 2 -and H 2 O 2 by macrophages did not increase after the administration of an aqueous extract from the fruiting body and mycelia of Phellinus linteus.…”
Section: Discussionmentioning
confidence: 85%